Identity, Community, And Audience: How Wholly Owned Foreign Subsidiaries Gain Legitimacy In China - Li, Jiatao; Yang, Jing Yu; Yue, Deborah R. (Academy of Management Journal, 2007)
Conceptualizing different foreign entry modes as distinct organizational forms, we examine how wholly owned foreign subsidiaries (WOFSs) gain legitimacy in a host country. Drawing on the institutional and ecological perspectives, we build a legitimation framework based on the ideas of identity, community, and audience. Specifically, we identify dual sources of legitimating influences for these subsidiaries in China in 1979–95: foreign direct investment (FDI) communities, and host country public opinion. Our findings reveal that the legitimation and competition dynamics of FDI communities and Chinese acceptance of the organizational form both influenced adoption of wholly owned foreign subsidiaries in China.